Lyngbygruppens indsats for at redder jøder i Humlebæk og Gilleleje i oktober 1943 - Ulff-Møller, Jens (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
The rescue of about 7,000 Jews from Denmark to Sweden in October 1943 is legendary, and has become world-famous not least due to Aage Bertelsen’s book October 43. He and his wife headed the so-called Lyngby group that was hiding Jews before arranging their transportation to Sweden from Humlebak and Smidstrup (Gilleleje). The group consisted of two sections: First, Dr. Ebba Standbygaard headed a local resistance group related to the political party Dansk Samling, and to the sabotage organization Holger Danske and the SOE. The other section, to which Bertelsen belonged, consisted of high school teachers who had relations to Dansk Studiering, an organization aiming to distribute illegal information. Two Jews were important for the creation of the group. One was Walter A. Berendsohn, former professor of Scandinavian literature at the University of Hamburg, who settled in Lyngby in 1933 after Hitler came to power in Germany. The other was the veterinarian David Sompolinsky, a member of the ultra orthodox synagogue in Copenhagen. It is possible to determine that members of the ultra orthodox synagogue and their relatives and friends were among the approximately 700 Jews rescued by the Lyngby group. The group collaborated with a group of doctors and students, and therefore the number of people who were rescued by the Lyngby group may be higher. Bertelsen escaped to Sweden on September 16, 1943, and he became the chairman of the board of trustees of the Danish School in Lund. Due to informers, most of the Lyngby rescuers fled to Sweden, and some ended up in concentration camps. Two of them were mistreated so badly that they died shortly after the liberation.